Stock Traders Perception towards Stock Market Variability and Trading - Mittal , A.K.; Aggarwal, Vimal K. (Gyan Management Journal, 2014)
Stock market traders encounter the market variability so frequently that they assign different reasons and causes for the variability. Understanding the real cause and intensity of variability is just not possible for stock traders. Market fluctuations are so abrupt and wide that even the technical indicators fail to show the reversal sign quickly. Most of the traders fail to take benefits of market variability due to ’FEAR and GREED’ factors. When market swings downward, fear develops among investors and restrains them from buying at lower levels. Similarly greed plays its role in bullish market and restrains the investors from booking profits by selling at high levels. Analysis of the data collected shows that most of the stock traders fail to take right decision of buying and selling during the opportunities created by variability, largely due to their inherent risk aversion trait.